Moodle e-learning Platform in the Faculty of Veterinary Medicine Cluj-Napoca, Romania. Weaknesses and Advantages in the Virtual Environment as seen by Teachers - Alexandru Ion GUDEA; Tudor TĂNASE; Nicoleta GUDEA (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Veterinary Medicine)
The present paper approaches, using a Google survey, the main aspects of the usage of the e-learning platform as perceived by teachers of the Faculty of Veterinary Medicine Cluj-Napoca, Romania. Several aspects related to the way they use it, the perceived advantages of the usage of Moodle platform as well as some drawbacks are highlighted.  Based on the given responses in a survey administered in early 2024, some causes are indicated along with some possible solutions in the attempt to implement the faculty-wide usage of the LMS Moodle platform. A serious warning signal is addressed to the Management team of the Faculty, as, in accordance to the teachers' responses, it holds the key to changes in the curricular approach in a team effort that requires a strong collaboration among teachers- management and students.